Microplastics in the Langat River Basin, Malaysia: sources, loads and fate - Chen, Hui Ling (2023)
Microplastics (commonly defined as plastic particles smaller than 5mm in size) are widely recognised as a global concern. However, studies of the occurrence of microplastics in freshwater systems, particularly in Malaysia, are limited.